Income Tax Treaty Policy in the 21st Century: Residence vs. Source - Wells, Bret; Lowell, Cym H. (Columbia Journal of Tax Law, 2014)
The United States has repeatedly attempted to stop tax base erosion for almost the entire post-World War I era, and yet the same problems exist today. The need for fundamental tax reform is front-page material in the major newspapers with the US transfer pricing rules and US multinationals portrayed as public enemy #1. The OECD this month issued a report entitled “Addressing Base Erosion and Profit Shifting,” and in a competing fashion several important developing countries have initiated their own pact to develop cooperative strategies on these issues outside of the framework of the OECD and UN. The attached manuscript studies the historical record and sets forth a competing model for dealing with these matters which pre-dated the existing model treaties and transfer pricing paradigm. This earlier paradigm was offered by the International Chamber of Commerce’s but was prematurely abandoned by the League of Nations in favor of the existing paradigm. In light of the fact that the existing paradigm has failed so miserably, the earlier proposal should be re-considered. In the inevitable re-examination process, there will be a fascinating range of political, economic, and business issues to be addressed. Tax administrations will need to ascertain how their resources could be redeployed to foster economic growth. MNEs will need to assess the impact of new treaty concepts on their global effective tax rate planning models. The critical question is who will initiate the evolution to come. All countries are anxious to protect their respective tax bases. At the present time, it appears that the BRICS and Source Countries have planted their stake in the sand, rejecting the existing order and declaring an intention to update the rules that apply to their own tax base defense. The OECD appears to be principally driven by the need to defend its Member country tax bases, hoping, no doubt, that BRICS and Source Countries will ultimately follow its lead. Whichever organization emerges as the new-found thought leader on these questions, it is now time to give the original International Chamber of Commerce recommendation a fair consideration on its merits (which, interestingly, addresses the current concerns of BRICS and Source Countries).